Associative words in the symmetric group of degree three - Plonka, E. (Algebra and Discrete Mathematics, 2013)
Let G be a group. An element w(x, y) of the absolutely free group on free generators x, y is called an associative word in G if the equality w(w(g₁, g₂), g₃)=w(g₁, w(g₂, g₃)) holds for all g₁, g₂ ∈ G. In this paper we determine all associative words in the symmetric group on three letters.